You are not alone: social capital and risk exposure in rural Ethiopia - Wossen, T.; Falco, S. di; Berger, T.; McClain, W. (Springer, 2016)
This paper examines the impact of shocks on food security and the insurance role of social capital and informal social networks. In particular, by combining household panel data, weather data, self-reported shocks and detailed social capital information, the paper investigates the insurance role of social capital against covariate and idiosyncratic shocks. Our results suggest that both covariate and idiosyncratic shocks increase the prevalence of food insecurity. However, households with a higher stock of social capital were able to smooth consumption. We also found that food consumption is not insured through social capital when a shock affects the whole risk-sharing network. Moreover, we show that formal policy interventions such as access to consumption credit and safety nets are the only effective ways of insuring food consumption when a shock affects the entire risk-sharing network.